Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4038/slja.v26i2.8320
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized study comparing the standard weight-based method and a novel method based on combined width of index, middle and ring fingers for ProSeal laryngeal mask airway size selection in paediatric patients

Abstract: Introduction: Appropriate size selection of ProSeal laryngeal mask airway (PLMA) is an important prerequisite for successful use of the device. Size of PLMA is often selected based on weight of patients. We aimed to determine whether combined width of patient's index, middle and ring fingers could be used as an alternative to weight-based selection of appropriate size of PLMA. Materials and methods: In this prospective randomized study, 102 patients aged 6 months to 10 years were included. Patients were alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…The width of the index, middle, and ring fingers was also used to determine the size of in the prospective randomized study by Mathew et al . [ 11 ] in pediatric patients. They reported that the size of PLMA was the same in both methods in 66.66% of the children, but was inconsistent in 33.34%, with only one size in those whose weight was borderline.…”
Section: Discussionmentioning
confidence: 99%
“…The width of the index, middle, and ring fingers was also used to determine the size of in the prospective randomized study by Mathew et al . [ 11 ] in pediatric patients. They reported that the size of PLMA was the same in both methods in 66.66% of the children, but was inconsistent in 33.34%, with only one size in those whose weight was borderline.…”
Section: Discussionmentioning
confidence: 99%